(untitled) (Raparin Journal of Humanities (RJH), 2024)
This article sheds light on criminal protection of the environment, which is concerned with the environmental protection from various types of pollution and destruction. Muslim jurists, have been discussing specific ways and means of preserving the environment and protecting it from the destructive causes that lead to an imbalance in the environmental system. Meanwhile, the Kurdistan Regional Parliament has discussed the achievement of this issue through the special law on criminal protection entitled "Law on Environmental Protection and Improvement No. (8) of 2008". This research evaluates the legal articles related to achieving criminal protection of the environment contained in the aforementioned law in Islamic jurisprudence, to the extent of which these articles are compatible with Islamic jurisprudence. The research consists of an introduction and four sections, and ends with a conclusion that includes the most important findings and recommendations. "Among its prominent findings: The law’s provisions generally align with Islamic Sharia’s objectives and principles in environmental protection, including safeguarding environmental elements, prohibiting corruption, and imposing penalties on offenders. However, from an Islamic Sharia perspective, this law has some shortcomings, such as not criminalizing certain environmentally harmful acts, lacking deterrent punishments for some serious crimes, overlooking criminal liability for legal entities, and a weak religious dimension in its texts. Finally, it offers suggestions for improvement in light of Islamic Sharia’s rulings and objectives in environmental preservation."